A new species of the genus Macrorhyncolus Wollaston, 1873 (Coleoptera: Curculionidae: Cossoninae) from China - Omar, Youssef M.; Zhang, Runzhi; Davis, Steven R. (Zootaxa, 2017)
Following recent taxonomic study, Macrorhyncolus spinosus sp. nov. is described from China. Earlier, Macrorhyncolus included four species, M. crassiusculus, M. crassitarsis, M. littoralis and M. ventilaginis. A key is presented to all known species of Macrorhyncolus in the Palaearctic Region and China. Illustrations of diagnostic characters of the new species are provided. Macrorhyncolus spinosus is winged, has larger eyes, the rostrum is longer than wide and has a median furrow in the basal half, extending to the vertex, and striae 9 and 10 remain separate from base to apex.